Katherine Mansfield and Elizabeth von Arnim - Kimber, Gerri; Maddison, Isobel; Martin, Todd (Katherine Mansfield studies ;, 2019)
By bringing the work of Mansfield and von Arnim together - including on matters of artistry, on mourning, on gardens, on female resistance - this book establishes shared preoccupations in ways that refine and extend our knowledge of writing in the period.